Pengaruh Sumber Daya Manusia, Sistem Pengendalian Intern Pemerintah, dan Audit Keuangan Daerah terhadap Kualitas Laporan Keuangan - Agustiawan, Agustiawan; Putri, Annie Mustika; Saputra, Yoni (Universitas Nahdlatul Ulama Surabaya, 2021)
The purpose of this study is to examine the effect of human resources, the government's internal control system and regional financial audits towards the quality of financial statements. The population in this study was all employees in the Office of the Regional Financial and Asset Management Agency (BPKAD) Riau Province whilst the sample was 116 respondents. The sampling method in this research is census sampling. The data used were primary data, which was completely done by using survey methods with questionnaires and the processing method used was multiple linear regression. The result of this study conveys that the variables of human resources, internal government control systems and regional financial audits affect the quality of financial statements.